Did the "Bologna Process" Achieve Its Goals? 20 Years of Empirical Evidence on Student Enrolment, Study Success and Labour Market Outcomes - Martina Kroher; Kathrin Leuze; Stephan L. Thomsen; Johannes Trunzer (Institute of Labor Economics (IZA), 2021)
In 1999, the "Bologna Process" was initiated to improve higher education enrolment, study success and students' employability across Europe, mainly by introducing the two-cycle degree structure of Bachelor (BA) and Master (MA). More than 20 years later, we examine whether these goals were met by reviewing quantitative articles from sociology and economics. We find that the literature is surprisingly small, selective, and ambiguous. While enrolment seems to have increased in countries implementing the reform more quickly, the evidence on study success is mixed and hardly available regarding student mobility. The results on employment outcomes are more consistent, with BA graduates having lower labour market returns than graduates with MA or traditional degrees. Altogether, studies often do not allow for causal conclusions and only provide a fragmented picture, which makes evidence-based adjustments in reform implementation difficult. This calls for further research using better data, more state-of-the-art methods and deeper theoretical reasoning.
Keywords: I23; I28; Z13; 330; universities; education; employment; inequality; economics; sociology